Compositional evaluation of selected agro-industrial wastes as valuable sources for the recovery of complex carbohydrates. (November 2016) - Vojvodić, Aleksandra; Komes, Draženka; Vovk, Irena; Belščak-Cvitanović, Ana; Bušić, Arijana
Abstract: Re-utilization of various agro-industrial wastes is of growing importance from many aspects. Considering the variety and complexity of such materials, compositional data and compliant methodology is still undergoing many updates and improvements. Present study evaluated sugar beet pulp (SBP), walnut shell (WS), cocoa bean husk (CBH), onion peel (OP) and pea pods (PP) as potentially valuable materials for carbohydrate recovery. Macrocomponent analyses revealed carbohydrate fraction as the most abundant, dominating in dietary fibres. Upon complete acid hydrolysis of sample alcohol insoluble residues, developed procedures of high performance thin-layer chromatography (HPTLC) and high performance liquid chromatography (HPLC) coupled with 3-methyl-1-phenyl-2-pyrazolin-5-one pre-column derivatization (PMP-derivatization) were used for carbohydrate monomeric composition determination. HPTLC exhibited good qualitative features useful for multi-sample rapid analysis, while HPLC superior separation and quantification characteristics. Distinctive monomeric patterns were obtained among samples. OP, SBP and CBH, due to the high galacturonic acid content (20.81%, 13.96% and 6.90% dry matter basis, respectively), may be regarded as pectin sources, while WS and PP as materials abundant in xylan-rich hemicellulose (total xylan content 15.53%, 9.63% dry matter basis, respectively). Present study provides new and valuable compositional data for different plant residual materials and a reference for the application of established methodology. Graphical abstract: Highlights: Content of structural polysaccharides ranged from 42% to 68% dmb Developed HPTLC useful for rapid, multiple sample qualitative analysis of monomers Pre-column PMP derivatization HPLC-UV method resulted in reliable quantitative data Monomeric profiles of structural carbohydrates revealed their distinctive composition. SBP, CBH and OP sources of pectic substances, while WS and PP of hemicelluloses